The Influence of External Factors on Immunomodulatory Consumption Practices in Health Workers During The Covid-19 Pandemic - Widayanti, Ni Putu; Laksmita W., Ayu Saka; Apriyanthi, Desak Putu Risky Vidika (JURNAL INFO KESEHATAN, 2025)
The need for the consumption of immunomodulators is very important to support the body’s immunity of health workers during the Covid-19 pandemic to remain prime in providing services. Because the helath of healthcare workers during the pandemic determines the service that will be provided to patients. This study aims to analyze the influence of external factors on the practice of consuming immunomodulators in health workers at the Denpasar City Health Center. This research is non-experimental research using a cross-sectional method. The population of the research is 550 people and the sample size used in this study amounted to 232 people who have met the inclusion criteria. The results obtained for R square were 0.605 which indicated that the support of the head of the Health Center, family support, co-worker support, and advertising promotion had a large role, namely as much as 60.5% in influencing the practice of consuming immunomodulators in health workers. The R-value obtained in this study was 0.778; F of 86,852; and p of 0.000 (p<0.05) where the hypothesis is accepted, which means that there is a significant influence of external factors on the practice of consuming immunomodulators. There is a significant relationship between the support of the head of the Health Center, family support, co-worker support, and advertising promotion on the practice of consuming immunomodulators. External factors greatly influence healthcare workers' attitudes toward maintaining their health, one of which is their responsiveness in consuming immunomodulators during the pandemic.